The parasitic travel of Margaritifera margaritifera in Atlantic salmon gills: from glochidium to post-larva - Castrillo Arias, Pedro Antonio; Bermúdez Pose, Roberto; Varela Dopico, Catarina; Quiroga Verdeal, María Isabel; Ondina Navarret, María Paz (Aquaculture Reports)
The larval development of the endangered freshwater mussel Margaritifera margaritifera (L.) represents one of the most unique parasitism among naiads, in which larva parasite the fish gills for several months. Despite the importance of this parasitic phase to successfully culture the freshwater mussel, the larval morphogenesis remains understudied. To describe the parasitic larval development and metamorphosis, Atlantic salmon (Salmo salar L.) were exposed to glochidia, sampled periodically to visualize the gills by stereomicroscopy and light microscopy and results were summarized throughout three developmental stages. Once attached to the fish gills, glochidia changed their morphology within the first days and acquired an intermediate stage termed mushroom larva due to the presence of the mushroom body and the zip membrane, both structures are transitory and distinctive of this long-lasting parasitism. The zip membrane, located at the valve cleft, may play a unique role in the isolation and acquisition of non-particulate nutrients from the fish, while the mushroom body of the mantle accumulates abundant intracytoplasmic lipid droplets. After 200 days, a successful metamorphosis was evidenced by the formation of a complete set of post-larval organs, pointing to the acquisition of different functionality, which will be essential for the settlement and deposit-feeding into the riverbed. Among the post-larval organs, the byssal complex of the post-larval foot was described for the first time at the end of the parasitic stage of naiads. In conclusion, this study provides an overview of the larval morphogenesis of M. margaritifera, from glochidium to post-larva, essential for understanding the parasitic interaction between the freshwater mussel larva and the fish host. Moreover, the morphological techniques and the hallmarks described might be applicable to optimize and monitor the larval developmental status during one of the most critical stages of the captive breeding programmes of endangered freshwater mussels ...